Прэже съжения всего мира – о некоем типе ошибок в древнерусских списках Евангелия - Szwed, Zofia (Acta Polono-Ruthenica, 2018)
This article is devoted to a special kind of errors made by the scribes of the Old Russian Books of the Gospels. These are erroneous wordings which create the impression of being correct, since they constitute existing words, in wording and form, similar to the original ones, but which nevertheless alter the meaning of the text. The article presents mechanisms of occurrence of such errors and also shows that modification of meaning caused by erroneous writing could have different degree. The contribution of the writer’s consciousness to the development of error was taken into account in the research. An attempt was made to use the results of the analysis of errors of a given type to formulate conclusions regarding the way the scribe works and his degree of professionalism.